Fetal kidney length as a parameter for determination of gestational age from 20th week to term in healthy women with uncomplicated pregnancy - Peter, Monalisa; Nayak, Ajit Kumar; Giri, Prajna Paramita; Jain, Manju Kumari (International Journal of Research in Medical Sciences, 2017)
Background: Accurate assessment of gestational age is pivotal to give quality maternity care. Ultrasonographic fetal biometry is the most widespread method used to establish GA. Sonographic biometric parameters commonly used are Crown rump Length (CRL), Biparietal diameter (BPD), Head circumference (HC), Abdominal circumference (AC) and Femur length (FL). Fetal Kidney Length (FKL) is one of nontraditional parameter and more accurate method of GA estimation than BPD, FL, HC and AC after 24th week of gestation. This study evaluates role of FKL in estimation of GA and compared its accuracy with other established biometric indices. Methods: Present study is a cross sectional study and includes healthy women who were certain of their LMP with prior regular menstrual cycles with uncomplicated pregnancy between 20 weeks of gestation to term. Maximum length of anyone single fetal kidney is measured from upper pole to lower pole at least thrice and mean of the measurements was taken. The data has been analyzed in SPSS-21 version and Microsoft word, excel have been used to generate graphs, tables etc. Results: Linear regression equation showed kidney length could predict gestational age with an accuracy ±9.048 days and predictability when combined with other biometric indices was ±8.299 days. Conclusions: The study shows good correlation between gestational age derived from FKL and gestational age from established biometric indices like BPD, HC, AC, and FL.FKL can be combined with the other four biometric indices to give a fair estimation of gestational age.